Et si les stratégies d’apprentissage des étudiants et leurs perceptions envers l’évaluation des apprentissages avaient un lien avec l’ajustement académique dans un contexte de persévérance aux études universitaires? - Nancy Barbeau; Éric Frenette; Marie-Hélène Hébert (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The objective of this systematic literature review is to verify the links between student learning strategies, perception of learning assessment (attraction and belief) and academic adjustment in the context of retention in Higher Education. Based on Gough's (2007) systematic literature review approach, 21 scientific papers published between 2006 and 2017 which is presenting studies with Higher Education students were selected. The results confirm the existence of links between learning strategies and perception of learning assessment, between learning strategies and academic adjustment, but no links between perception of learning assessment and academic adjustment. There is also a lack of study that can confirm or invalidate the links between the three concepts.